The living lab approach and ocean citizenship in sustainable development of the blue economy and food security - Abentin Estim; Ching Fui Fui @ Faihana Ching Abdullah; Sitti Raehanah Muhamad Shaleh; Madihah Jafar Sidik; Saleem Mustafa (Journal of Hunan University, 2024)
his article elaborates on different perspectives on the blue economy and suggests the importance of a Living Lab approach to support sustainable blue growth in sectors such as seafood security. This discussion highlights the growing dependence of the world on marine ecosystem services and the need to inculcate key elements of sustainability in ocean ecosystems while deriving socioeconomic benefits. A marine Living Lab serves the purpose of engaging different stakeholders, including professionals, managers, coastal communities, and entrepreneurs, in blue economy projects. For it to function effectively, an inclusive organizational structure and the identification of key goals and performance indicators should be clearly defined. The challenges of delivering outcomes from heterogeneous stakeholders deserve to be addressed to solve these problems and to adopt practically feasible models for specific sectors of the blue economy. Ocean citizens committed to pro-environmental activities will synergize and contextualize their roles in marine sustainability and find a voice to influence policymaking institutions. When acting in sync, the marine Living Lab and ocean citizenship programs can create new knowledge that can be applied to developing a blue economy. The study identified that higher education institutions have the means and resources to co-develop innovations in real-world contexts. The inclusivity expected in the Living Lab projects will increase the familiarity of a broad range of stakeholders with increasingly important areas of emerging technology. This study is intended to address the so-called ‘complexity avoidance’ syndrome constraining the sustainable growth of small-scale ocean-based enterprises. Thus far, the application of such technologies has been limited to academia and a limited number of aquaculture and fisheries industries. This study represents the first attempt to blend the blue economy with seafood security in the Living Lab domain.